Seismic response of RCC dam including dam foundation interaction - Thanoon, Huda A.M.; Noorzaei, J.; Jafaar, M. S.; Thanoon, Waleed. A.; Malathy, R. (Journal of Structural Engineering, 2024)
A study for predicting the structural response of a 76.8 m high Kinta Roller Compacted Concrete (RCC) dam located in Malaysia under dynamic loads has been conducted by using the finite element method. The dam body, bedding rock media and the contact area in between have been modelled using coupled finite and infinite elements. The study covers the seismic response of Kinta Dam focusing on the non-linear behaviour of the dam-foundation interface and its effect on stress distribution. Nonlinear constitutive models of the thin layer interface elements are evolved to trace different modes of yielding along dam-foundation interface to simulate debonding, slipping and crushing mechanism of the thin layer interface element. The results obtained indicate the yielding of thin layer interface elements before the RCC material in the dam body followed by a redistribution of stresses to the dam body as well as the foundation bedding. The plasticity was spread upwards with the progress of excitation time. The plastic deformation in thin layer interface is allowed to occur whenever seismic stresses exceed the envelope presented by modified Mohr-Coulomb failure criteria and it is mainly in the slipping mode at thin layer interface elements.